Improvement on the Key Element of Flexible U-Shaped Steel Support and Its Field Applications - Zhili Su; Shengguo Jing; Wenbing Xie; Qingteng Tang; Xingkai Wang (Advances in Civil Engineering)
In China, there are a significant numbers of soft rocks roadways in underground coal mines. The roofs of these roadways are generally highly fractured, and traditional bolt installation does not provide sufficient supporting capacity. Hence, U-shaped steel support has gained popularity, and the key influential factor of steel support is the lock unit between its mechanical structures. The commonly used two-slotted splint lock unit can experience eversion and splitting and resulted in overall instability. To overcome the limitation, a “surface snap-in” lock unit was developed. Based on experimental results, it was found that the relationships of bearing capacity and deformation of two lock unit types were similar under same loading conditions. The ultimate bearing capacity of surface snap-in lock unit was lower than the two slotted splint unit. Although, its overall stability and flexibility were better. On the other hand, screw bolts of both unit types exhibited increase or decrease with the compressional deformation of steel support. The maximum stress along the screw bolt of two-slotted splint lock unit was 1.6 to 1.8 times of the surface snap-in lock unit. Based on the findings, the combination of two lock unit types was proposed and used at Peigou coal mine. Results show that the proposed design can effectively manage the roadway deformation while preventing the steel support damage. This in turn can reduce the associated supporting cost as the steel support can be recycled.